Sosialisasi Pengaruh Stunting Terhadap Perkembangan dan Pertumbuhan Anak Usia Dini di Desa Sibabat - Astuti Mulyani, Eva; Maftalia Fifadhilni, Shendy; Ella Maida, Dila; Falyanita Sari, Fitri; Sartika, Dewi; Tri Lestari, Sulis; Nur Salman, Amar; Umpuhilal, Ilham; Dly, Lulu; Zahratul Khusna, Nurul (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
The KUKERTA program is knowing the procedures for implementing the KUKERTA program at the University of Riau in Sibabat Village, which has been implemented optimally or not, and knowing the programs offered by students while running the KUKERTA program in Sibabat Village. Efforts promoted by KUKERTA students in the 2020 batch are to prevent stunting in children and provide education to parents so that they can pay more attention to the development and nutritional intake of children.